Investigation of structural and optical properties of pure ZnO and co-doped ZnO:Al:Mnx (x=1%, 2%, 3%, 5% at.) semiconductor thin films and electrical properties of produced diodes - Demirbilek, Nihat; Kaya, Mehmet; Yakuphanoğlu, Fahrettin (Gazi Univ, Fac Engineering Architecture, 2023)
In this work, undoped and co-doped ZnO:Al:Mn semiconductor thin films and p-type Si diodes were produced via sol-gel technique method. The morphological and optical properties of the produced thin films were investigated using SEM, XRD and UV-Spectrophotometer, respectively. It was observed that the crystal structure of the semiconductor samples had a hexagonal wurtzite structure and the forbidden energy gaps of the samples decreased with increasing Mn contribution. The experimental zero-feed current barrier height (Phi(b)(I-V)), rectification ratio, ideality factor and I-on/I-off parameters of the diodes were determined via the thermionic emission model. It was determined that the produced Al/p-Si/ZnO:Al:Mn/Al diode had high rectification ratio and I-on/I-off values of 1.56x10(5) and 1.54x10(4), respectively, and exhibited light-sensitive behaviour. Also, the capacitance barrier height (Phi(b)(C-V)), built-in voltage (V-bi), diffusion potential (V-d), donor concentration (N-d) and depletion layer width (W-d) values of Al/p-Si/ZnO:Al:Mn/Al diode were calculated via the C-2-V graph drawn under 1MHz frequency. The results show that the fabricated diodes can be used as photodiodes or photosensors in optoelectronic applications.
Saf ZnO ve katkılı ZnO:Al:Mnx (x=1%, 2%, 3%, 5% at.) yarı iletken ince filmlerin yapısal ve optiksel özellikleri ile üretilen diyotların elektriksel özelliklerinin araştırılması
Keywords: Semiconductor; ZnO; photodiode; optical properties; sol-gel